2019
DOI: 10.3390/antiox8120637
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of β-Carotene on Helicobacter pylori-Induced TRAF Expression and Hyper-Proliferation in Gastric Epithelial Cells

Abstract: Helicobacter pylori infection causes the hyper-proliferation of gastric epithelial cells that leads to the development of gastric cancer. Overexpression of tumor necrosis factor receptor associated factor (TRAF) is shown in gastric cancer cells. The dietary antioxidant β-carotene has been shown to counter hyper-proliferation in H. pylori-infected gastric epithelial cells. The present study was carried out to examine the β-carotene mechanism of action. We first showed that H. pylori infection decreases cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…Among dietary intervention as non-microbial or dietary approach targeted for H. pylori infection, quite several agents had been studied, including blueberry plants, ( 3 ) phytochemicals from fruits, ( 4 ) genistein from soy rich diet, ( 5 ) dietary antioxidant β-carotene or astaxanthin, ( 6 , 7 ) and n -3 polyunsaturated fatty acids ( n -3 PUFAs)-rich walnut. ( 8 ) Stimulated with significant cancer preventive outcome of walnut that n -PUFAs synthesizing Fat -1 transgenic mice synthesizing n -3 PUFAs such as DHA or EPA significantly resisted from chronic H. pylori -associated gastric carcinogenesis and walnut polyphenol extracts significantly inhibited interleukin-6 (IL-6)/Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) signaling via peroxisome proliferator-activated receptor γ (PPAR-γ)/suppressors of cytokine secretion (SOCS) 1 stimulation in gastric cells, ( 8 , 9 ) we put hypothesis that dietary intake of walnut ( Juglans regia L.) can reduce H. pylori -associated gastric carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Among dietary intervention as non-microbial or dietary approach targeted for H. pylori infection, quite several agents had been studied, including blueberry plants, ( 3 ) phytochemicals from fruits, ( 4 ) genistein from soy rich diet, ( 5 ) dietary antioxidant β-carotene or astaxanthin, ( 6 , 7 ) and n -3 polyunsaturated fatty acids ( n -3 PUFAs)-rich walnut. ( 8 ) Stimulated with significant cancer preventive outcome of walnut that n -PUFAs synthesizing Fat -1 transgenic mice synthesizing n -3 PUFAs such as DHA or EPA significantly resisted from chronic H. pylori -associated gastric carcinogenesis and walnut polyphenol extracts significantly inhibited interleukin-6 (IL-6)/Janus kinase (JAK)/signal transducer and activator of transcription 3 (STAT3) signaling via peroxisome proliferator-activated receptor γ (PPAR-γ)/suppressors of cytokine secretion (SOCS) 1 stimulation in gastric cells, ( 8 , 9 ) we put hypothesis that dietary intake of walnut ( Juglans regia L.) can reduce H. pylori -associated gastric carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…However, our previous study showed that a low concentration (0.5 and 1 µM) of β-carotene reduced ROS levels and inhibited NF-B activation, NF-B-regulated expression of tumor necrosis factor receptor associated factor (TRAF), and hyper-proliferation in H. pylori -infected gastric epithelial cells [ 49 ]. A low concentration of β-carotene (0.15 and 0.3 µM) inhibited peroxynitrite anion-induced lipid peroxide production in rat brain synaptosomes [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…β-carotene was able to block the H. pylori induced degradation of IκBα, thereby retaining NF-κB in the cytoplasm, preventing its nuclear translocation and activation of nuclear transcription targets, including TRAF1 and TRAF2 gene expression. Clinical prevention studies have suggested oral intake of β-carotene may decrease the risk of gastric cancer in H. pylori endemic areas by as much as 48% [ 85 ].…”
Section: Helicobacter Pylori -Virulence Factorsmentioning
confidence: 99%
“…The effect of CagA induced chronic atrophic gastritis and decreased secretion of vitamin C into the gastric lumen may explain, in part, the variable efficacy of dietary phytochemicals from fruit and vegetables in prevention studies of gastric dysplasia and adenocarcinoma. There have been positive [ 85 , 145 , 146 , 147 ], negative and equivocal results [ 148 , 149 , 150 , 151 , 152 , 153 ], some of which relate to study power and design, H. pylori virulence, endoscopic assessment, baseline histology, heterogeneity, controlling for other risk factors, assessment of plasma vitamin C status, dietary recall and length of follow-up [ 146 , 147 , 148 , 149 ]. For example, a pooled analysis was performed of 810 prospectively collected non-cardia gastric cancer cases and 1160 matched controls from East Asian countries (Korea, Japan, China), with associated H. pylori CagA status, demographic, lifestyle, smoking and dietary data.…”
Section: Vitamin C and H Pylorimentioning
confidence: 99%